Effects of Different Drying Methods on Drying Kinetics, Microstructure, Color, and the Rehydration Ratio of Minced Meat - Aksoy, Asli; Karasu, Salih; Akcicek, Alican; Kayacan, Selma (MDPI, 2019)
This study aimed to investigate the effect of different drying methods, namely ultrasound-assisted vacuum drying (USV), vacuum drying (VD), and freeze-drying (FD), on the drying kinetics and some quality parameters of dried minced meat. In this study, USV was for the first time applied to the drying of minced meat. The USV and VD methods were conducted at 25 degrees C, 35 degrees C, and 45 degrees C. The different drying methods and temperatures significantly affected the drying time (p < 0.05). The USV method showed lower drying times at all temperatures. The rehydration values of the freeze-dried minced meat samples were higher than those obtained by the USV and VD techniques. The samples prepared using USV showed higher rehydration values than the vacuum dried samples for all temperatures. The effects of the different drying techniques and drying conditions on the microstructural properties of the minced meat samples were investigated using scanning electron microscope (SEM). The USV method resulted in higher porosity and a more open structure than the VD method. Total color differences (Delta E) for VD, USV, and FD were 8.27-20.81, 9.58-16.42, and 9.38, respectively, and were significantly affected by the drying methods and temperatures (p < 0.05). Higher drying temperature increased the Delta E value. Peroxide values (PV) significantly increased after the drying process, and samples treated with USV showed lower PV values than the VD treated samples. This study suggests that USV could be used as an alternative drying method for minced meat drying due to lower drying times and higher quality parameters.
Keywords: ultrasound assisted drying; minced meat; SEM; microstructural; ULTRASOUND PRETREATMENT; ANTIOXIDANT ACTIVITY; PHENOLIC CONTENT; QUALITY; DEHYDRATION; TEMPERATURE; MUSHROOMS; BEHAVIOR; STORAGE; APPLE; Food Science & Technology